Then - Gleitzman, Morris (London : Puffin Books, 2009)
After Nazi soldiers commandeer their orphanage in Poland, young Felix escapes with his friend Zelda, but the safe places the pair finds to hide quickly turn dangerous, and the orphans must remain on the run to avoid capture and death in a concentration camp.
Young Adult.
Young Adult
Keywords: Holocaust, Jewish (1939-1945) -- Poland -- Juvenile fiction; Jews -- Poland -- Juvenile fiction; Orphans -- Juvenile fiction; Separation (Psychology) -- Juvenile fiction; Survival -- Juvenile fiction; World War, 1939-1945 -- Poland -- Juvenile fiction; Historical fiction; Holocaust, Jewish (1939-1945) -- Poland -- Fiction; Jews -- Poland -- Fiction; Orphans -- Fiction; Separation (Psychology) -- Fiction; Survival -- Fiction; World War, 1939-1945 -- Poland -- Fiction; Historical fiction; Holocaust, 1939-1945.; Jews -- Poland -- Fiction; Orphans -- Fiction; Separation anxiety in children -- Fiction; Survival skills -- Fiction; World War, 1939-1945 -- Poland -- Fiction; Poland -- History -- Occupation, 1939-1945 -- Juvenile fiction; Poland -- History -- Occupation, 1939-1945 -- Fiction; Poland -- History -- Fiction; Historical fiction